Odpowiedzi

2010-03-21T16:52:04+01:00
A)4x=3x-5
4x-3x=-5
x=-5

b)64+2x=46+x
2x-x=46-64
x=-18

c)3-x=-2x
-x+2x=-3
x=-3

d)4+3x=2+2x
3x-2x=2-4
x=-2

e)x+1/4=1/2+2x
x-2x=½-¼
-x=²/₄-¼
-x=³/₄ / :(-1)
x=-¾

f)3x+1/7=x-1
3x-x=-1-¹/₇
2x=-1¹/₇ / :2
x=-³/₄

g)1 3/4-3x=-3 1/4-4x
-3x+4x=-3¼ - 1¾
x=-5
2010-03-21T16:56:13+01:00
A. x=-5
b.x=-18
c.x=-3
d.x=-2
e.x=1/2-1/4 x=2/4-1/4 x=1/4
f.2x=-1-1/7 2x=-1 1/7 /:2 x=-4/7
g.x=3 1/4-1 3/4 x=13/4-7/4 x=1 2/4
2010-03-21T17:00:22+01:00
A) 4 x= 3x-5 / -3x
x = -5

b) 64+2x=46+x /-x
64+x = 46 / -64
x = -18

c) 3-x = -2x /+x
3 = -x / *(-1)
-3 = x
x = -3

d) 4+3x = 2+2x / -4
3x = -2+2x /-2x
x = -2

e) x+ 1/4 = 1/2 +2x / -x
1/4 = 1/2 + x / *2
1/2 = x
x = 1/2

f) 3x + 1/7 = x-1 / -x
2x + 1/7 = -1 / *7
2x + 1 = -7 / -1
2x = -8 / :2
x = -4

g) 1 3/4 - 3x = -3 1/4 -4x / +3x
1 3/4 = -31/4 -x / *4
7 = -12 - x / +12
19 = -x / *(-1)
-19 = x
x = -19